Studies on the IgA system of the horse - Vaerman, J. P. (1971)
Equine serum and secretions were found to contain a protein which cross-reacted with an antiserum against human IgA, but not with antisera against any other human immunoglobulin. The physicochemical properties of equine IgA resembled those of human IgA. IgA was found to be the immunoglobulin having the highest secretion vs serum concentration ratio in equine lacteal and salivary secretions, and to be the protein produced by the majority of immunoglobulin-containing cells in the lamina propria of the equine intestine.